A Community Engagement Model for Improving Teachers’ Competence in Developing Sundanese Instructional Materials in Primary Schools - Yudhie Suchyadi; Rini Sri Indriani; Nita Karmila; Resy A. Ghani (International Journal of Management, Innovation, and Education, 2026)
.